Criminal Aspects of Illegal Online Lending Practices in Indonesia - Yanta Karona Subakti; Rospita Adelina Siregar (International Journal of Health, Economics, and Social Sciences (IJHESS), 2025)
The economic crisis, the increasing needs of society, and the development of the internet and digital world are seen as a golden opportunity for official banks and large financiers to gain greater profits. Banks that have existed so far provide loan facilities through applications and internet networks without collateral or guarantees and without complicated conditions. The interest is still affordable, the conditions are also in accordance with Bank Indonesia (BI) regulations and are under the supervision or supervision of the Financial Services Authority (OJK). In addition, there are also large investors, both individually and syndicated and in collaboration with banks that have made a financial technology (fintech) breakthrough in the form of providing online loan facilities or known to the public as "pinjol". This online loan is favored and utilized by people who need money quickly because the conditions are very easy, without collateral or collateral, and directly disbursed to the customer's bank account (borrower). Along with the development of online loans, there are also online loans that are not licensed and operate outside the stipulated provisions or often called illegal online loans. Based on the results of the research, these illegal online loans have mushroomed and operate in violation of criminal provisions and other applicable provisions such as the application of high interest rates, fraud, intimidating collection methods, and dissemination of personal data. If examined closely, the practice of illegal online lending is full of legal violations, especially criminal law, which makes its customers victims. Intimidation and the dissemination of personal data have caused suffering for customers caught up in illegal online loans, even causing someone in Jambi to commit suicide some time ago. This journal will discuss the various criminal offenses that occur in illegal online lending practices and the efforts that can be made to eradicate illegal online lending practices. The author hopes that this Journal can contribute ideas for lawmakers so that in the end a law regulating online loans can be created that provides justice, benefits, and legal certainty for the community, especially users of online loan services.